A Retrospective Study of Pattern of Cranio-Cerebral Injuries Due to Road Traffic Accident in a Tertiary Care Hospital - Vaidehi Singh; Siddesh Revpla Channabasappa (Indian Journal of Forensic Medicine & Toxicology, 2021)
Head injury is defined as sudden injury due to an external force that affects the functioning of brain. It may beeither caused by sudden blow or impact (closed head injury) or by an object penetrating the skull (Penetrating injury).The common causes of head injury include road traffic accidents, fall from height and assault. The mortality fromhead injury is reported to be between 1-2% of death from all the causes. Not only it is one of the major causes ofdeath in young adults but also may cause permanent disability in survivors. The importance of head injury as a publichealth problem cannot be overstated. In the studies of Road Traffic accidents provide valuable data for implementingeffective emergency services to reduce the trauma related mortality and strengthening legal measures in peak hoursof fatal accidents. We aimed to study, pattern of injuries especially cranio- cerebral injuries occurring in vehicularaccidents. Patients case records with history of head injury and MLC records of victims of road traffic accidentreported to Saveetha hospital, Chennai from 1st Jan 2019 to 31st Dec 2019 period were analysed retrospectively.Out of total 1846 Road Traffic Accidents cases reported to Emergency Medicine department, SaveethaMedical college hospital, Chennai, 10.40% cases had history of head injury. The male/female ratio was9:1. Commonest age group affected was between 21-40 years involving 126 (65.62%n=192) cases. Fataltraumatic brain injuries were seen in 178 (92.70%, n=192) cases. Amongst 192 head injury cases, scalpinjury noted in 167 (86.97%) cases, most common bone fractured was temporal bone 94(48.95%), followedby other bone parts. The commonest variety of intracranial haemorrhage was subdural haemorrhage 173(n=192, 90.10%) followed by Subarachnoid haemorrhage and Extradural haemorrhage. In 26 (13.54%)patients of head injury, craniotomy surgery was done. The timings between 3PM to 6PM showed the highestnumber of cases accounting to 61.7% of the cases followed by 26.0% of cases between 6PM to 9PM. Thetwo-wheeler accidents accounted for 69.9% of the head injury cases followed by that due to other vehicles(16.7%)